Health Technology Assessment on the use of the Wearable Cardioverter Defibrillator in Patients with Myocardial Infarction and with ICD Explant - Cortesi, Paolo Angelo; Botto, Giovanni Luca; D'Angiolella, Lucia; Scalone, Luciana; De Ponti, Roberto; Boriani, Giuseppe; Mantovani, Lorenzo Giovanni (Farmeconomia. Health economics and therapeutic pathways, 2021)
The objective of the present work is to conduct a Health Technology Assessment (HTA) on the use of the Wearable Cardioverter Defibrillator (WCD) in patients at risk of Sudden Cardiac Arrest (SCA) following Myocardial Infarction (MI) or with an explanted Implantable Cardioverter Defibrillator (ICD).